Surgery for pediatric invasive fungal sinonasal disease. (17th December 2013) - Ardeshirpour, Farhad; Bohm, Lauren A.; Belani, Kiran K.; Sencer, Susan F.; Lander, Timothy A.; Sidman, James D.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To evaluate the management and outcomes of children with invasive fungal sinonasal disease treated with radical surgery. Study Design Retrospective case series. Methods From 1994 to 2007, 11 pediatric patients were identified with invasive fungal sinonasal disease treated surgically by the same pediatric otolaryngologist. Collected data included demographics, oncologic diagnoses, absolute neutrophil counts, symptoms, computed tomography scan findings, biopsy and culture results, surgical procedures, concurrent medical therapies, complications, and survival. Results The studied patient population consisted of four males and seven females with an average age of 10 years (range, 2–14 years). Six patients were diagnosed with acute lymphoblastic leukemia and five with acute myeloid leukemia, which included 10 cases of relapsed disease. The average number of severely neutropenic days prior to diagnosis of an invasive fungal infection was 18 (range, 8–41 days). Culture results demonstrated Alternaria in seven patients and Aspergillus in four. Nine patients underwent an external medial maxillectomy, five of which were bilateral, and six underwent septectomy. All 11 patients (100%) were cured of their invasive fungal sinonasal disease without relapse. Three patients eventually died from unrelated causes. Conclusions Invasive fungal sinonasal disease is a life‐threatening problem in immunocompromised children, especially with relapsed leukemia. Successful treatment depends on timely and aggressive surgical, antifungal, and supportive therapies. To our knowledge, this study represents the largest series of pediatric patients with invasive fungal sinonasal disease managed via an aggressive surgical approach with the best outcomes to date. Level of Evidence 4. Laryngoscope, 124:1008–1012, 2014